(untitled) - Green, Samuel B. (Boston, 2014)
The development of easy-to-use statistical software like SPSS has changed the way statistics is being taught and learned. Even with these advancements, however, students sometimes still find statistics a tough nut to crack. Using SPSS for Windows and Macintosh, 7/e, guides students through basic SPSS techniques using step-by-step descriptions and explaining in detail how to avoid common pitfalls in the study of statistics.
Keywords: SPSS (Tệp máy tính),Khoa học xã hội,SPSS (Computer file),Social sciences; Phương pháp thống kê,Statistical methods